(untitled) (Vietnam Journal of Community Medicine, 2026)
Mesenteric venous thrombosis (MVT) is a rare but life-threatening cause of acute abdominal pain, particularly when associated with congenital protein C deficiency. We present a 65-year-old Vietnamese man with acute epigastric and periumbilical pain and loose stools. Though initially hemodynamically stable, he showed signs of peritonitis. Laboratory findings revealed leukocytosis and elevated D-dimer. Contrast-enhanced CT confirmed complete thrombosis of the superior mesenteric vein, partial portal vein thrombosis, and bowel wall edema. Protein C activity was reduced to 50%. The patient underwent emergency laparotomy with resection of one meter of necrotic bowel and creation of a double-barrel ileostomy. He received postoperative anticoagulation with enoxaparin, later switched to apixaban. Discharged in stable condition on postoperative day 14, he showed resolution of portal vein thrombosis at one-month follow-up. This case underscores the importance of early imaging, recognition of inherited thrombophilia, and timely surgical and anticoagulant therapy in managing MVT.